1995
DOI: 10.1111/j.1600-0447.1995.tb09543.x
|View full text |Cite
|
Sign up to set email alerts
|

Life satisfaction as a mediator between distressing events and neurotic impairment in a general population

Abstract: Quality of life and life satisfaction have often been investigated as concomitant variables of anxious and depressive symptoms as well as an outcome measure in psychotherapy research. In the present prospective survey, life satisfaction and stressful events function as independent variables predicting the development of neurotic disturbances in a general population. A random sample of 184 adults completed two quality of life surveys (1990 and 1992). Results showed that satisfaction in relevant life domains was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
0
13
0
3
Order By: Relevance
“…The results of these studies by Lewinsohn and his colleagues (1991) were corroborated and extended in a prospective study of 184 randomly selected community volunteers in which levels of life satisfaction assessed 2 years earlier significantly predicted the onset of Diagnostic and Statistical Manual (DSM)-diagnosed depressive, anxiety, and somatoform disorders (Baruffol et al, 1995). The authors concluded that low life satisfaction is a major risk factor for psychological disturbance.…”
Section: Predictive Validitymentioning
confidence: 87%
“…The results of these studies by Lewinsohn and his colleagues (1991) were corroborated and extended in a prospective study of 184 randomly selected community volunteers in which levels of life satisfaction assessed 2 years earlier significantly predicted the onset of Diagnostic and Statistical Manual (DSM)-diagnosed depressive, anxiety, and somatoform disorders (Baruffol et al, 1995). The authors concluded that low life satisfaction is a major risk factor for psychological disturbance.…”
Section: Predictive Validitymentioning
confidence: 87%
“…Low life satisfaction is associated with frustration in meeting personal life goals and standards and is connected with anxiety and depression as well as with some stress-related psychophysiological and somatoform disorders. (Baruffol et al, 1995). People tend to feel more satisfied when they perceive that their standards of fulfillment have been met, and they experience less satisfaction when they have not.…”
Section: Discussionmentioning
confidence: 99%
“…It is linked to pessimism, poor problem solving skills, and a variety of psychological symptoms (Olason & Roger, 2001). As dissatisfaction persists, probability of developing depression is increased (Baruffol et al, 1995;Diener & Larsen, 1993).…”
Section: Goal Directedness In Relation To Life Satisfaction Psycholomentioning
confidence: 99%
“…Çünkü alanyazında yetişkinler üzerinde yapılan araştırmalar incelendiğinde heyecan arayışı ve (örn., Çelik & Turan 2016; Stegman 2010) ve proaktif kişiliğin (örn., Greguras & Diefendorff, 2010;Cunningham & de la Rosa, 2008) yaşam doyumu ile ilişkili olduğu görülmektedir. Ayrıca, benlik saygısının yaşam doyumu (Giannakopoulos 1994; Stegman 2011), proaktif kişilik (Şahin 2006) ve heyecan arayışı (Baird 1981) ile pozitif açıdan ilişkili olduğu, depresyonun proaktif kişilik (Greenglass, Schwarzer & Taubert 1999;Pasikowski, Sek, Greenglass & Taubert 2002;Greenglass, Fiksenbaum & Eaton 2006;Greenglass 2006) ve heyecan arayışı (Carton, Jouvent & Widlocher 1992) ve yaşam doyumu (Lewinsohn Redner & Seeley 1991;Hong & Giannakopoulos 1994;Baruffol, Gisle & Corten 1995) ile negatif açıdan ilişkili olduğu görülmektedir. Ayrıca, dışadönüklüğün heyecan arayışı (Aluja, Garcia & Garcia 2003), yaşam doyumu (Diener et al 1999) ve proaktif kişilik (Bateman & Crant 1993) ile pozitif açıdan ilişkili olduğu belirtilmektedir.…”
Section: Heyecan Arayışının Yaşam Doyumu İle Proaktif Kişilik Arasındunclassified
“…Diğer taraftan alanyazında bu araştırmada ele alınan bu üç değişkenin depresyonla ilişkisinin de araştırıldığı araştırmaların olduğu görülmektedir. Yapılan araştırma sonuçlarında depresyon seviyesi yüksek olan bireylerin düşük olan bireylere göre yaşamlarından daha az doyum aldıkları tespit edilmiştir (Lewinsohn, Redner & Seeley 1991;Hong & Giannakopoulos 1994;Baruffol, Gisle & Corten 1995). Benzer şekilde Carton, Jouvent ve Widlocher (1992) yaptığı çalışmasında heyecan arayışı ile depresyon arasında negatif yönde bir ilişkinin olduğunu bulmuştur.…”
Section: Fig 1 Heyecan Arayışının Baskıcı Rolüunclassified